Estudio de Posicionamiento de las PYMES Inclusivas del Cantón Guaranda, provincia bolívar, año 2017 - Chacha Chacha, Angel David (2018)
This research was developed with the purpose of knowing the level of positioning that exists in the small and medium enterprises of the Guaranda Canton, that at the moment there has not been any type of investigation related to this topic. Taking into account that the main results were given in the investigation. For this we move to different places of the small and medium enterprises of the Guaranda Canton, obtaining a result of participation level and positioning in the market, in addition most of the legally constituted companies are duly controlled by public institutions: (SRI, MSP, GADCG, MAGAP) to offer quality products to consumers. In addition, the descriptive, qualitative, quantitative and field research and exploratory types were used; the surveys were applied to small and medium enterprises registered in the Ministry of Industry and Productivity (MIPRO). Considering that it is essential to carry out this investigation, in order to determine an analysis of participation and positioning within the market, in the same way the SMMs of the Canton of Guaranda generate jobs for the families of the sector, thus improving the economic development of society. From the information acquired from small and medium enterprises, which determines that the companies have their own property, this avoids a lease expense, thus obtaining an acceptable profit. There is also a high percentage of skills with micro, small and medium enterprises within the locality and outside the locality. To carry out analyzes and interpretations, the conclusions and recommendations of the present project were determined, fulfilling the established objectives.